Penerapan Pembebanan di Luar Kemampuan Mukallaf dalam Fatwa DSN-MUI: Analisis Usul Fikih Empat Mazhab Sunni dan Mu’tazilah - Hidayat, Enang (TAWAZUN: Journal of Sharia Economic Law, 2026)
The examination of DSN–MUI fatwas regarding obligations, sanctions, and the responsibilities of customers through the lens of the principle of imposing obligations beyond the capacity of the mukallaf (taklīf mā lā yuṭāq) needs to be conducted to address whether DSN–MUI fatwas are consistent with the principle of taklīf mā lā yuṭāq or whether they impose burdens beyond the parties’ capacity. The purpose of this study is to identify the principle of taklīf mā lā yuṭāq as applied in DSN-MUI fatwas and its implementation according to the usul fiqh theories of the four Sunni schools and the Mu’tazilah. This research is normative Islamic law research in the doctrinal domain, using conceptual, philosophical, and comparative approaches. Primary sources include the usul fiqh literature of the four Sunni schools and the Mu’tazilah. Data were collected through document studies. The results indicate that although DSN-MUI fatwas do not explicitly mention the principle of taklīf mā lā yuṭāq, they apply it implicitly in the five analyzed fatwas, namely Fatwa No. 04/DSN-MUI/IV/2000, No. 17/DSN-MUI/X/2000, No. 47/DSN-MUI/II/2005, 48/DSN-MUI/II/2005, and No.129/DSN-MUI/VII/2019. All these fatwas show a consistent pattern: obligations are imposed only on those capable, parties who are incapable or affected by force majeure are not burdened, sanctions are applied only to those capable but intentionally delay, and facilitation is provided through rescheduling and reduction of burdens. Overall, these fatwas are consistent with the principle of the capacity of the mukallaf as emphasized in the usul fiqh of the four Sunni schools and the Mu’tazilah.